Ion channels in the central regulation of energy and glucose homeostasis - Sohn, Jong-Woo (Frontiers in Neuroscience, 2013)
Ion channels are critical regulators of neuronal excitability and synaptic function in the brain. Recent evidence suggests that ion channels expressed by neurons within the brain are responsible for regulating energy and glucose homeostasis. In addition, the central effects of neurotransmitters and hormones are at least in part achieved by modifications of ion channel activity. This review focuses on ion channels and their neuronal functions followed by a discussion of the identified roles for specific ion channels in the central pathways regulating food intake, energy expenditure, and glucose balance.